Energies beyond the state: anarchist political ecology and the liberation of nature - Mateer, Jennifer; Springer, Simon; Locret-Collet, Martin; Acker, Maleea (Rowman & Littlefield, 2022)
"This volume contributes to advancing an 'ecology of freedom,' which can critique current anthropocentric environmental destruction, as well as focusing on environmental justice and decentralized ecological governance"--
Keywords: Aufsatzsammlung; Anthropogener Einfluss; Landschaftszerstörung; Natur; Umweltpolitik; Sozialökologie